(untitled) (Scientific journal of the Fergana State University, 2025)
In this article, the conclusions of scientific research on the ideological-artistic function of the artistic detail in the work, the importance of the detail in the structure of the work are highlighted. The idea of ​​studying the artist’s skill to pay more attention to the structural tasks of the gallery of details or details was discussed. For this purpose, a number of details have been thoroughly analyzed in the story "Jodi" by Khurshid Dostmuhammad. Their importance in elucidating the artistic idea of ​​the work and revealing the character of the heroes was noted.Key words: artistic detail, "Jodi" work, structure of the work, mosquito detail, Guillotine, symbolic image, artistic image, character of heroes